Indications and outcomes of tracheostomy in intensive care unit - Rahman, Mukhlesur; Begum, Mahmuda; Khan, Mujibul Hoque; Anwar, Mostsfa Mahfuzul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Tracheostomy is a commonly performed surgical procedure in the intensive care unit (ICU) in which creation of a stoma between the skin and the anterior wall of the trachea where there is need for prolong mechanical ventilation. Tracheostomy has considered a safe procedure in ICU but has been found to lead to life threatening complications intra and post operatively. Methods: This is a cross sectional study, was carried out in ICU, Chittagong Medical College Hospital, Chattogram from January 2018 to December 2019. A total of 120 patients irrespective of age and sex whose tracheostomy has done after admission in ICU by ENT surgeons. Results: Out of 120 patients maximum 34 (28.33%) were from 21-30 years age group and male to female ratio was 1.79:1, male patients were 77 (64.16%) and female patients were 43 (35.83%). The most common indication for tracheostomy in ICU was head injury and history of RTA 34 (28.33%) followed by post-operative case of intracranial space occupying lesion 30 (25%). Post tracheostomy complication was surgical emphysema 4 (3.33%). The rate of complication of tracheostomy in ICU was 10.83% in this study. Regarding benefits of tracheostomy over endotracheal tube in ICU, we found that 100% patients had greater comfort. Conclusions: Tracheostomy in ICU is an important and safe procedure if prolonged endotracheal in tubation is advised for varying underlying causes.